Research-to-Resource: Designing Singing Assessments for Classroom Use. (October 2019) - Nichols, Bryan E.
Research has provided several scales for valid assessments of singing skills. Singing voice development and singing accuracy (tunefulness) are frequent objectives targeted by teachers in music classrooms. Teachers and directors may find established scoring systems useful for implementing formative or summative assessments. This research-to-resource article provides examples for teachers to use or adapt to promote and encourage singing growth.